Effect of cross-linking and hydration on microscale flat punch indentation contact to collagen-hyaluronic acid films in the viscoelastic limit. (15th July 2020) - McManamon, Colm; Cameron, Andrew; de Silva, Johann P.; Daly, Ronan; O'Brien, Fergal J.; Cross, Graham L.W.
Abstract: The properties of the extracellular matrix (ECM) have profound impact upon cell behaviour. As an abundant protein in mammals, collagen is a desirable base material to engineer an ECM tissue scaffold, but its structural weakness generally requires molecular crosslinking or incorporation of additional ECM-based macromolecules such as glycosaminoglycans. We have performed microscopic indentation to test collagen films under dry and aqueous conditions prepared with different levels of physical and chemical crosslinking. Our technique isolates intrinsic properties of the poro-viscoelastic matrix in a regime minimizing the influence of drainage hydrodynamics and allows direct measurement of the effect of hydrating a specific sample. A doubling of the effective stress-strain stiffness under crosslinking could be directly correlated to structural changes in X-ray diffraction spectra, while electron microscopy revealed possible fibril bridging mechanisms explaining observed toughness. Overall, an intrinsic viscoelastic stress-strain response of collagen under various conditions of cross-linking was observed for both dry and wet conditions, with the latter most affected by indentation rate. Under creep testing, a three order of magnitude increase in dynamic compliance and factor three reduction in relaxation time was found going from the dry to hydrated state. When fitted to a simple viscoelastic model, crosslinking showed a tendency to decrease relaxation time in both states, but reduced dynamic compliance only in the hydrated case. This suggests a reduced role of virtual crosslinks under hydration. This is the first study reporting consistent mechanical testing of dry and hydrated ECM-derived biomaterials, accessing the intrinsic material mechanics under in vivo -like conditions. Statement of Significance: This manuscript presents new insights into the effect of crosslinking on mechanical properties of dry and hydrated collagen intended for tissue scaffolding applications. A novel microscopic indentation technique allowed testing of the poro-viscoelastic matrix isolated in a regime minimizing the influence of drainage hydrodynamics, so direct comparison of the effect of hydration on the intrinsic material behaviour to could be made. A variety of experimental techniques including X-ray diffraction, infrared spectroscopy, and scanning electron and atomic force microscopy were used to augment the mechanical testing. The results of creep testing were numerically analysed using a four-component viscoelastic model. This is the first mechanical testing of dry and hydrated ECM-derived biomaterials, accessing the intrinsic material mechanics under in vivo-like conditions. Graphical abstract: Image, graphical abstract